Aspek Hukum Perjanjian dalam Sistem Shopee Spinjam pada Kegiatan Kredit Online di Indonesia - Vivi Sylvia Purborini (Postgraduate University of Merdeka Malang, 2022)
This research aims to analyze the legal concept of a credit agreement when viewed from the Civil Code and how the concept of the Shopee SPinjam credit agreement on the Shopee application. This research is a normative legal research with a statutory approach method and a comparative approach. The results showed that the credit agreement on Shopee SPinjam when viewed from civil law is in accordance with what is regulated in the Civil Code and related regulations such as the implementing rules of Shopee SPinjam. So that from the review of civil law the position of the Shopee SPinjam credit agreement is considered valid. The legal consequences of the Online Money Lending Agreement in the perspective of Civil Law have binding legal force for the parties as agreements in general. However, there is something that must be considered, namely the interest rates of both because with high interest rates the agreement can be canceled. The government through Bank Indonesia or the Financial Services Authority must immediately make regulations regarding restrictions on loan interest or regulations related to Reasonable Interest Rates for loans and financial technology. The determination of interbank bidding rates will reduce the complexity of financial contracts by encouraging the standardization of the use of benchmark interest rates on debt securities and/or loans with floating interest rates, rupiah interest rate derivatives and also for valuation of financial instruments. In addition, the government must ensure supervisory authority and provide protection for users and providers of financial technology with certaintyDOI: https://doi.org/10.26905/mlj.v3i1.9262